Author’s cinematograph of new Hollywood: The issue of director’s self-fulfillment - Pogrebniak, Galyna P.; Gavran, Iryna A.; Honcharuk, Serhii M.; Mykhalov, Volodymyr Ya.; Kot, Halyna M. (Linguistics and Culture Review, 2021)
The paper is devoted to the problems of director’s self-fulfilment in the cinematograph of New Hollywood. The study examines such a unique phenomenon of the artistic culture of the 20th century as American author’s cinematograph. The relevance of this study is determined by the trends in the development of New Hollywood, which have radically changed the essence of modern cinematograph. The purpose of the study is to identify the specifics of New Hollywood cinema, which resonated in the work of modern Hollywood directors as an influential and competitive area. The main emphasis in this study is placed on the attempts of both historians and film theorists, as well as practitioners themselves to find clear boundaries between American independent and mass Hollywood cinematograph, as well as on the reasons why film critics and culturologists consider a particular American film to be independent, author’s, or mass cinema (the so-called mainstream). At the same time, the main areas and trends of American author’s cinematograph are studied from the point of view of director’s self-fulfilment. Examples from films by American directors and authors were analysed. Methods of scientific analysis, comparison, and generalisation were used in the study of the topic.